Comparative Effects of Miosta-H and Bodifors Biostimulants on Calves’ Blood Parameters and Non-Specific Immune Defense - Bobomurodov U.Ch.; Salimov Y.; Ahmad Tulqinovich Ibragimov (American Journal of Biomedicine and Pharmacy, 2026)
This scientific article presents the results of a comparative study on the effects of the biostimulants Miosta-H and Bodifors on calves’ blood parameters and their non-specific immune defense mechanisms. The administration of Miosta-H demonstrated a significant positive effect on the morphological and biochemical parameters of calf blood, as well as on the phagocytic, lysozyme, and bactericidal activities of non-specific immune components in blood serum compared to the control group. A similar effect was also observed in calves treated with Bodifors. The findings indicate that both biostimulants have a pronounced influence on blood parameters and enhance both cellular and humoral immunity in calves.